PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGELOLA DAN MENGEMBANGKAN KEGIATAN EKSTRAKURIKULER DI SEKOLAH - Khamim, Nur; Najmul Hidayat, Ayi; Kurniawati, Nia; Aji Fachrurroji, Fahmi (Penerbit Lafadz Jaya, 2025)
This study aims to analyze the role of school principals' leadership in managing and developing extracurricular activities in secondary schools. The research focuses on the strategies and approaches employed, the challenges encountered, and the positive impacts of extracurricular activities on students’ development and the school environment. This research adopts a qualitative approach using a case study method. Data were collected through in-depth interviews, direct observation, and document analysis, and were analyzed thematically. The findings indicate that the principal plays a strategic role as a planner, facilitator, motivator, and evaluator in the implementation of extracurricular programs. Various strategies, including student interest mapping, training for teacher advisors, external collaboration, and the use of information technology, were applied to enhance activity quality. Despite challenges such as limited budget, time constraints, and student participation issues, principals managed to overcome them through innovative and collaborative approaches. Extracurricular activities have been proven to positively impact students by improving social skills, leadership abilities, self-confidence, and by fostering a positive and participatory school climate.